Relationship between bone marrow-derived CD34^＋ cells expressing interleukin-5 receptor messenger RNA and asthmatic airway inflammation - 毛辉 王曾礼 李富宇 刘春涛 雷松 (Chinese medical journal, 2004)
Background Asthma is clinically related with the degree of eosinophilic inflammation. How asthmatic airway inflammation is affected is still poorly understood. So the effects of bone marrow-derived hematopoietic cells expressing CD34(CD34^+) and interleukin-5 (IL-5) receptor messenger RNA(IL-5R mRNA^+) on asthmatic airway inflammation were investigated.Methods Balb/c mice were sensitized and challenged by ovalbumin (OVA) to establish an asthmatic model while control mice were sensitized and exposed to sterile saline. The mice were killed at different time points after being challenged by OVA and sterile saline. Then, bronchoalveolar lavage fluid (BALF), peripheral blood (PB) and bone marrow (BM) were prepared. Eosinophils in PB(PBEOS) and BALF (BALFEOS), nuclear cells in BALF, PB and BM were counted. By flow cytometry,the percentage of CD34^+ cells to nucleated cells in PB, BM and the relative number of CD34^+ cells in PB (PBCD34^+) and BM ( BMCD34^+) were calculated. Immunocytochemistry and in situ hybridization were used to investigate the hematopoietic cells with co-localized expression of CD34 and IL-5R mRNAin BM ( BMCD34^+ IL-5R mRNA^+), The percentage of BMCD34^+ IL-5R mRNA^ + to BMCD34^+ was calculated. Results Twelve hours after challenge by OVA, BALFEOS and PBEOS in the experimental group were significantly higher than those in the control group (P<0.01). Twenty-four hours after OVA challenge, BALFEOS, PBEOS and BMCD34^+ IL-5R mRNA^+ were elevated maximally, ignificantly different from those in the control group (P<0.01). Forty-eight hours after OVA challenge, BALFEOS and BMCD34^+ IL-5R mRNA^+ were still significantly higher than those of the controls (P<0.01). The other markers reverted to normal. In 60 mice, BMCD34^+ IL-5R mRNA^+ was closely correlated with the BALEOS,PBEOS, BMCD34^+ and BMCD^+(%) (P<0.05). Conclusions The amount of CD34^+ cells expressing IL-5R mRNA increased in the BM of asthmatic model mice, which favors eosinophilopoiesis and eosinophilic airway inflammation. A signal pathway exists between the lungs and the bone marrow, which is involved in the initiation and maintenance of asthmatic airwav inflammation.